Analysis of the Implementation of Automatic Feeding IoT Systems on the Productivity of Catfish (Clarias sp.) Aquaculture - Talitha Amanda; Sandra Dewi Elizabet Kaunang; Miswanto; Muhammad Chairil Apriandi; Raden Faqih (Jurnal Penelitian Pendidikan IPA, 2025)
Feed represents the largest expense in catfish (Clarias sp.) aquaculture, accounting for up to 70% of production costs. Improving feed efficiency is therefore essential to enhance productivity and reduce operational costs. This study developed and evaluated an Internet of Things (IoT)-based automatic feeder designed for small-scale aquaculture. The novelty of this research lies in the integration of Arduino and BARDI components into an affordable autofeeder system that supports precision feeding management for smallholders. Two feeding methods were compared: manual feeding and automatic feeding using the developed IoT-based system. Productivity indicators measured included Feed Conversion Ratio (FCR), Specific Growth Rate (SGR), Survival Rate (SR), and water quality. Results showed that conventional feeding produced lower FCR (0.29) and higher SGR (18.50%/day) during the early growth phase. Survival rates were relatively low (60–63%) but improved in later weeks. Most water quality parameters remained within the optimal range, except for temperature, which slightly exceeded tolerance levels and contributed to mortality. Although the IoT-based feeder requires further refinement to match manual feeding performance, it demonstrates strong potential to improve feeding accuracy, reduce labor dependency, and promote sustainability in small-scale catfish aquaculture.